O papel do protocolo Agroambiental Etanol Verde na conectividade de paisagem: um analise temporal - Chagas, Renato Luciani (2022)
The State os São Paulo Government (Brazil) and the Sugar Cane Industry Association signed together, in 2007, the Sugar-Alcohol Sector Agri-environmental Protocol. The document foresaw the end of the fire managment technique of the cane fields and the water sources and riparian forest. However, this public policy didn’t estabilish clear goals for conservation actions. In this context, our work had as an objective to analise this protocol’s role based on three main questions: (i) Do the actions of the sugar-alcohol sector that signed the protocol induced the increase of forest patches in riparian forests that are Permanent Preservation Areas (PPA)? (ii) After the protocol’s signature, was there an increase of functional connectivity? (iii) What is the increase in functional connectivity with all the permanent preservation areas restored? We chose the Araras city (State of São Paulo, Brazil) as the land model for the research. We compared the evolution of riverside PPA based on the Functional connectivity Indexes IIC e PC for the years of 2006, 2020 and we analised these indexes on a hypothetical scenery with all the PPA restored. The results showed a 27,3% increase in vegetal cover from 2006 to 2020 in PPA. Through those years, few forest patches showed areas larger than 100 ha, with only six forest patches in 2006 (2,59%) and eight in 2020 (2,17%). For the IIC Index, the hypothetical scenarios with the PPA restoration scenarios is significantly diferent from the years of 2006 and 2020 (p<0,001). Nonetheless, there is no significant difference in between the 2006 and 2020 connectivity (p = 0,244). As for the PC index, there is a significant difference between the three studied scenarios. We concluded that the actions proposed by the Agri-environmental Group’s Protocol, even increasing the total forest and connectivity area, may be insuficient to affect the functional connectivity in a positive way and, consequently, the natural landscape resilience. That happens because the sugar cane cultivation is intensively managed and needs of complementary Public Policies, as the use of low-impact pesticides, to ensure the biodiversity conservation and a soil use planning to increase the permeability matrix.